Navigating risk: Analyzing the effects of climate change and political connections on bank financing access for the agricultural sector - Silviana Pebruary; Hadi Ismanto; Fatchur Rohman; Dwi Falihaturrohman (Banks and Bank Systems)
Climate change has become a major focus of discussion around the world. The impact of climate change has been felt in various sectors, including banking. This study aims to analyze the effect of climate change and political connections on bank financing and financial stability in the Indonesian banking sector. The study used a sample of banks listed on the Indonesia Stock Exchange. The data used in the study were 2,379 observations, taken from 2010 to 2023. Hypothesis testing was performed using the fixed effects regression model (FEM) with robust standard error. The results show that climate change has a significant negative impact on bank financing and indicate that banks should consider the risks associated with climate change when making financing decisions. In addition, political connections have a negative effect on bank financing, implying that banks tend to reduce financing to politically connected firms, possibly due to concerns about poorer risk management. On the other hand, product diversification showed no significant effect in either model. These findings highlight the importance of considering environmental and political factors in banks’ financing strategies to enhance financial stability amid the challenges posed by climate change and political dynamics. This study provides new insights for regulators and practitioners in formulating policies. AcknowledgmentsThe greatest appreciation is conveyed to the Directorate General of Higher Education, Research, and Technology, Ministry of Education, Culture, Research, and Technology, which has provided funding support for this research through a principal research grant with contract number 108/E5/PG.02.00.PL/2024. Thanks are also expressed to the Higher Education Service Institute (LLDIKTI) Region 6 and the Institute for Research and Community Service (LPPM) Unisnu Jepara, Indonesia, for their continuous support and facilitation during the research process.